(untitled) (Journal of the College of Basic Education, 2022)
The aim of the research is "Imam Ali’s recitation, peace be upon him, in Lisan al-Arab by Ibn Manzoor" The words contained in the holy Quranic verses, and an indication of how Imam Ali read them in particular or With the consent of the other readers to read it, documenting it in the chapters, and mentioning its numbers and the places in which it was mentioned. In the Holy Qur’an, although it is few in number, as we will see later, it constitutes a linguistic phenomenon worthy of study. And compiling them in the field of Quranic readings that the researchers did not study according to the limits of our knowledge because Ibn Manzoor mentioned them.